Análisis de los niveles de comprensión de lectura crítica en las pruebas Saber 11 desde la perspectiva de la experiencia docente (2024)
Therefore, based on the reflection and problematization of the test results, five semi structured interviews were conducted with language teachers in order to investigate and reflect on the perspectives of teachers regarding the results of the Saber 11 tests in the area of critical reading language. Thus, a case study is carried out to identify the perspectives, problems, practices and opportunities for improvement that teachers propose for the teaching and learning of critical reading in the classroom.